Strategi Guru Pendidikan Agama Islam dalam Optimalisasi Media Pembelajaran untuk Menumbuhkan Minat Belajar - Aulia, Salshabila; Siswanto, Siswanto; Mukti, Saepul (Paedagogie: Jurnal Pendidikan dan Studi Islam, 2026)
The use of instructional media is an essential factor in creating engaging learning experiences and fostering students' interest in learning. However, the use of instructional media in Islamic Religious Education (IRE) remains suboptimal due to limitations in school facilities and teachers' competencies in utilizing instructional media effectively. This study aimed to describe the availability of instructional media, the strategies employed by IRE teachers in utilizing instructional media, and the challenges encountered in its implementation at SDN Sawah Kulon. This study adopted a qualitative approach with a descriptive design. The participants consisted of one IRE teacher, one vice principal, and several students selected through purposive sampling. Data were collected through observations, interviews, and documentation and analyzed using the Miles and Huberman interactive model, including data condensation, data display, and conclusion drawing. The findings revealed that instructional media at SDN Sawah Kulon were relatively adequate and were utilized through visual, audiovisual, and technology-based media according to the characteristics of the learning materials. Their use created more varied learning experiences, enhancing students' attention, interest, and active participation. The main challenges included limited internet access, inadequate supporting facilities, and teachers' competencies in optimizing instructional media. The study concludes that effective utilization of instructional media, supported by adequate facilities and teacher competence, contributes to more engaging learning and promotes students' interest in learning. These findings imply the need to strengthen teachers' competencies and improve school facilities to support more effective, innovative, and student-centered Islamic Religious Education.